PENGARUH PEMBERIAN JUS TOMAT TERHADAP KADAR GULA DARAH SEWAKTU PADA PASIEN HIPERGLIKEMIA - Almita Mila Susanti; Rina Puspita Sari; Siti cholifah S. Chasanah (Nusantara Hasana Berdikari, 2021)
Hyperglycemia can lead to decreased secretion resulting in insulin can increase insulin resistance. One alternative non-pharmacological treatment that can be used to reduce blood sugar levels is by using juice therapy. Juice therapy that can be used to treat diabetes mellitus is using tomatoes. Aim : The purpose of this literature review is to view and review articles related to the effect of giving tomato juice on blood sugar levels in elderly patients with hyperglycemia. Research Methods: Data obtained from electronic databases namely Google Scholar, Pubmed, Plos One, Science Direct between 2014 and 2019. Results: This literature study found 10 articles that fit the inclusion and exclusion criteria. From the review of the article, it is known that there is an effect of giving tomato juice to blood sugar levels when in hyperglycemia patients. Discussion: Based on the results of a literature review review of 10 articles, there is an effect of giving tomato juice to blood sugar levels when in hyperglycemia patients.